Design of Consumer Participative Device for Smart Grid Initiative - Lukman Rosyidi; Khoirul Umam (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
This paper will discuss about design of consumerparticipative device for smart grid initiative. Indonesia conditionis taken as the case, because smart grid initiative will depend onobject and environment condition. It is found that electricityprovider has difficulties to provide Advance MeteringInfrastructure (AMI), and that will be the area where consumermost probably be able to contribute for smart grid. As consumerdevice, it should be designed to give additional benefits forconsumer at affordable cost. Functionality requirements of thedevice for customer benefits are mapped. A smart meteringdevice is designed and proposed, which has capability to collectdata and report to electricity provider via IP network, withoutinterfering existing provider’s traditional meter. It is based on alow cost microcontroller with GSM/GPRS communicationcapability and optional autoswitch function to alternative sourceof energy. The experiment is done by making the deviceprototype. It shows that customer benefits and cost constraintcan be achieved with proper design of the device, to make feasiblethis consumer participative device concept for smart gridinitiative.